Novel screen printing plate made of novel material capable of being locally imidized
Form local amineization areas through metal mesh and polyester mesh, polyimide anterior driver coating and ion beam treatment, solve the problem of limited accuracy and short life of existing network versions, and achieve high precision, wear resistance New online version of sex and long life.
Patent Information
- Application Number
- CN202411596133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing screen production process has limited accuracy, short life, complex process flow, and the edge sealing area affects the screen life.
A composite of metal mesh and polyester mesh is used, combined with a polyimide precursor coating liquid, to form a local imidization area through ion beam bombardment and high-temperature heating, and finally a new screen plate is prepared through high-temperature lamination and laser cutting.
It improves the wear resistance, flexibility and service life of the screen, simplifies the process flow, enhances the interface bonding strength, ensures the production of high-precision graphics, and is suitable for industrial printing and electronic manufacturing in high-stress and harsh environments.
Smart Images

Figure CN119348282A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of screen printing, in particular to a novel screen printing made of a novel material capable of partial imidization. Background Art
[0002] The field of screen printing technology mainly involves the design and preparation of templates in the fields of printing, electronic manufacturing and precision coating. This field covers aspects such as screen design, material selection, manufacturing process and application. The screen is the core part of screen printing. Through the screen, ink, paste or other materials can be accurately transferred to the surface of the substrate to form a specific pattern or functional layer. In electronic manufacturing, screens are widely used in the production of circuit boards, touch screens, batteries and other devices. High-precision printing technology is used to achieve precise transfer of complex graphics and circuits. With the development of science and technology, the innovation of screen materials and manufacturing technology has continuously improved printing accuracy, durability and adaptability, and promoted the manufacture of a variety of high-end products.
[0003] The traditional screen making process uses a combination of photosensitive emulsion and metal mesh to produce graphics through exposure and development. However, this method not only has limited accuracy, but also has a short lifespan of the screen. With the development of technology, the current mainstream screen making process is to compound the metal mesh and PI film through high-temperature hot pressing, then use photosensitive emulsion for edge sealing, and finally complete the graphic plate making through laser cutting. Although this method improves accuracy, the process is complicated, and the edge sealing area still affects the lifespan of the screen. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a new type of screen made of a new type of material that can be partially imidized.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a new type of screen made of a new type of material that can be partially imidized, and the preparation method of the screen comprises the following steps:
[0006] S1, compounding the metal mesh and the polyester mesh, compounding the metal mesh with a thickness of 100 microns and the polyester mesh on a laminating device, using a polyethylene film with a thickness of 10 microns as an adhesive, and during the compounding process, ensuring that the metal mesh and the polyester mesh are flat, avoiding any wrinkles or bubbles, to obtain a composite mesh material;
[0007] S2, preparation of polyimide precursor coating liquid, in a reaction kettle, a polyimide precursor, a thermal bridging agent and a catalyst are mixed in a mass ratio of 2:1:0.1, and stirred at a speed of 2000 rpm for 30 minutes using a high-speed stirrer to ensure uniform mixing. After the stirring is completed, the mixed solution is heated to 80 degrees Celsius and maintained for 1 hour to make the coating liquid reach an optimal coating viscosity, thereby obtaining a polyimide precursor coating liquid;
[0008] S3, coating the composite mesh material with a polyimide precursor, and evenly coating the polyimide precursor coating liquid on the surface of the composite mesh material on an automatic scraper. After the coating is completed, a composite mesh coated with a polyimide precursor is obtained;
[0009] S4, preliminary baking and curing, in which the composite mesh coated with the polyimide precursor is baked in a hot air circulation baking device to partially cure the polyimide precursor to form a preliminary solid film, and then baked to obtain a partially cured composite mesh;
[0010] S5, ion beam regional bombardment, in the vacuum ion beam bombardment equipment, the partially solidified composite mesh surface is bombarded with ion beams, and the bombardment parameters are set to ion energy of 1000 eV and beam current density of 0.5 mA / cm 2 , the time is controlled within 15 minutes, the bombardment of the ion beam acts selectively on the target area, changing the chemical reactivity of each area, preparing for the subsequent imidization treatment, and obtaining the composite mesh treated with the ion beam;
[0011] S6, local high-temperature secondary heating, performing local high-temperature heating treatment on the composite mesh treated by the ion beam, using an infrared heating device to heat the target area to 250 degrees Celsius, and maintaining it for 5 minutes, so as to promote the imidization reaction of the polyimide precursor in each area, and after heating, obtain a composite mesh with a local imidization area;
[0012] S7, ion beam assisted imidization treatment, on the composite mesh with local imidization area, ion beam equipment is used again for auxiliary treatment to further control the depth and range of imidization reaction, the ion beam energy is increased to 1200 eV, and the beam density is controlled at 0.7 mA / cm 2 , the treatment time is extended to 20 minutes. After this step, the chemical structure of the imidization area is more stable, and a composite mesh yarn is obtained after ion beam assisted treatment.
[0013] Preferably, it also includes: S8, precise forming of the polyimide film, in which the composite mesh that has undergone ion beam assisted treatment is subjected to overall high-temperature pressurization treatment in a high-temperature pressing device, the temperature is set to 300 degrees Celsius, the pressure is set to 10 MPa, and the duration is 30 minutes. Through high-temperature pressurization, the polyimide film is fully formed on the entire surface of the composite mesh, and has excellent wear resistance and structural stability, thereby obtaining a formed polyimide film composite mesh.
[0014] Preferably, it also includes: S9, laser cutting pattern, in which the formed polyimide film composite mesh is cut according to a pre-set pattern in the laser cutting equipment, the laser power is set to 20W, the cutting speed is 0.1 m / s, and the cutting accuracy is controlled at ±10 microns. After laser cutting, a polyimide film composite mesh with a high-precision pattern is obtained.
[0015] Preferably, the method further includes: S10, finished product screen inspection and trimming, quality inspection and trimming of the polyimide film composite mesh with high-precision graphics, using a high-precision microscope to detect the graphics accuracy, check for flaws or cracks, repair or reprocess unqualified areas to ensure product quality, and obtain a new screen product that meets high-precision standards after inspection and trimming.
[0016] Preferably, in step S1, the temperature of the pressing equipment is set to 150 degrees Celsius, the pressure is 5 MPa, and the pressing time is controlled to 30 minutes.
[0017] Preferably, in step S3, the scraping speed of the automatic scraping equipment is controlled at 0.5 m / min, and the scraping thickness is controlled at 20 μm, ensuring that the coating liquid covers the entire mesh surface without bubbles or unevenness.
[0018] Preferably, in step S4, the baking temperature of the hot air circulation baking equipment is set to 150 degrees Celsius, and the baking time is 60 minutes.
[0019] 1. Compared with the prior art, the present invention adopts a combination of polyimide precursor, thermal bridging agent and catalyst, which makes it easier to achieve imidization conditions in the screen making process, enhances the wear resistance and flexibility of the material, and prolongs the service life. By directly scraping the polyimide precursor on the metal mesh, after baking and local high-temperature secondary heating, a polyimide film is formed, thereby greatly simplifying the process flow. In addition, using laser cutting technology, the polyimide film can be accurately cut to produce high-precision graphics to meet the needs of fine printing.
[0020] 2. Compared with the prior art, the present invention greatly improves the interfacial bonding strength of the polyimide film through the synergistic effect of ion beam bombardment and high-temperature heating, so that the adhesion between the film and the metal mesh is significantly enhanced. This enhanced interfacial bonding not only improves the stability of the screen under high stress conditions, but also prevents the delamination or shedding phenomenon that may occur during use. In addition, the precise control ability of the ion beam allows the imidization process to occur only in a specific area, avoiding excessive processing or material waste, thereby further improving production efficiency and material utilization. The screen produced by this method performs well in resistance to chemical corrosion and thermal deformation, can adapt to more harsh working environments, and is particularly suitable for industrial printing and electronic manufacturing fields that require high precision for a long time. This improved durability and reliability significantly extends the service life of the screen, reduces the replacement frequency and maintenance costs, and further enhances the economy and practicality of the process.
[0021] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the written description, claims, and drawings.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The present invention provides a preparation process diagram of a novel screen made of a novel material that can be partially imidized. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1, a novel screen made of a novel material capable of partial imidization, the preparation method of the screen comprising the following steps:
[0027] S1, compounding the metal mesh and the polyester mesh, compounding the metal mesh with a thickness of 100 microns and the polyester mesh on a laminating device, using a polyethylene film with a thickness of 10 microns as an adhesive, and during the compounding process, ensuring that the metal mesh and the polyester mesh are flat, avoiding any wrinkles or bubbles, to obtain a composite mesh material;
[0028] S2, preparation of polyimide precursor coating liquid, in a reaction kettle, a polyimide precursor, a thermal bridging agent and a catalyst are mixed in a mass ratio of 2:1:0.1, and stirred at a speed of 2000 rpm for 30 minutes using a high-speed stirrer to ensure uniform mixing. After the stirring is completed, the mixed solution is heated to 80 degrees Celsius and maintained for 1 hour to make the coating liquid reach an optimal coating viscosity, thereby obtaining a polyimide precursor coating liquid;
[0029] S3, coating the composite mesh material with a polyimide precursor, and evenly coating the polyimide precursor coating liquid on the surface of the composite mesh material on an automatic scraper. After the coating is completed, a composite mesh coated with a polyimide precursor is obtained;
[0030] S4, preliminary baking and curing, in which the composite mesh coated with the polyimide precursor is baked in a hot air circulation baking device to partially cure the polyimide precursor to form a preliminary solid film, and then baked to obtain a partially cured composite mesh;
[0031] S5, ion beam regional bombardment, in the vacuum ion beam bombardment equipment, the partially solidified composite mesh surface is bombarded with ion beams, and the bombardment parameters are set to ion energy of 1000 eV and beam current density of 0.5 mA / cm 2 , the time is controlled within 15 minutes, the bombardment of the ion beam acts selectively on the target area, changing the chemical reactivity of each area, preparing for the subsequent imidization treatment, and obtaining the composite mesh treated with the ion beam;
[0032] S6, local high-temperature secondary heating, performing local high-temperature heating treatment on the composite mesh treated by the ion beam, using an infrared heating device to heat the target area to 250 degrees Celsius, and maintaining it for 5 minutes, so as to promote the imidization reaction of the polyimide precursor in each area, and after heating, obtain a composite mesh with a local imidization area;
[0033] S7, ion beam assisted imidization treatment, on the composite mesh with local imidization area, ion beam equipment is used again for auxiliary treatment to further control the depth and range of imidization reaction, the ion beam energy is increased to 1200 eV, and the beam density is controlled at 0.7 mA / cm 2 , the treatment time is extended to 20 minutes. After this step, the chemical structure of the imidization area is more stable, and a composite mesh yarn is obtained after ion beam assisted treatment.
[0034] In this embodiment, it also includes: S8, precise forming of the polyimide film, in which the composite mesh that has undergone ion beam assisted treatment is subjected to overall high-temperature pressurization treatment in a high-temperature pressing device, the temperature is set to 300 degrees Celsius, the pressure is set to 10 MPa, and the duration is 30 minutes. Through high-temperature pressurization, the polyimide film is fully formed on the entire surface of the composite mesh, and has excellent wear resistance and structural stability, thereby obtaining a formed polyimide film composite mesh.
[0035] In this embodiment, it also includes: S9, laser cutting pattern, in the laser cutting equipment, the formed polyimide film composite mesh is cut according to a pre-set pattern, the laser power is set to 20W, the cutting speed is 0.1 m / s, and the cutting accuracy is controlled at ±10 microns. After laser cutting, a polyimide film composite mesh with a high-precision pattern is obtained.
[0036] In this embodiment, it also includes: S10, finished product screen inspection and trimming, quality inspection and trimming of the polyimide film composite mesh with high-precision graphics, using a high-precision microscope to detect the graphics accuracy, check for defects or cracks, repair or reprocess unqualified areas to ensure product quality, and after inspection and trimming, a new screen product that meets high-precision standards is obtained.
[0037] In this embodiment, in step S1, the temperature of the pressing equipment is set to 150 degrees Celsius, the pressure is 5 MPa, and the pressing time is controlled to 30 minutes.
[0038] In this embodiment, in step S3, the scraping speed of the automatic scraping equipment is controlled at 0.5 m / min, and the scraping thickness is controlled at 20 μm, ensuring that the coating liquid covers the entire mesh surface without bubbles or unevenness.
[0039] In this embodiment, in step S4, the baking temperature of the hot air circulation baking equipment is set to 150 degrees Celsius, and the baking time is 60 minutes.
[0040] Experimental methods:
[0041] Abrasion resistance test: Tested in accordance with GB / T 9867-2008 Determination of wear resistance of plastic film and sheet. Use Taber abrasion tester, select CS-10 grinding wheel, and apply 500g load. The experimental conditions are rotation speed of 60 rpm, sample size of 100mm×100mm, grinding wheel revolutions set to 500 revolutions, test environment temperature of 23±2℃, relative humidity of 50±5%. The test steps include fixing the sample on the Taber abrasion tester, starting the equipment after selecting the appropriate grinding wheel and load, and recording the mass loss (mg) of the sample after 500 revolutions as the abrasion resistance result.
[0042] Tensile strength test: The tensile strength test is carried out in accordance with GB / T 1040.3-2006 Determination of tensile properties of plastics Part 3: Film and sheet. The test equipment is an electronic tensile testing machine equipped with a 500N sensor. The experimental conditions are a tensile speed of 50mm / min, a sample size of 10mm in width, a thickness based on the actual sample, and a length of 100mm. The test environment temperature is 23±2℃ and the relative humidity is 50±5%. The test steps include cutting the sample according to the regulations, fixing it in the fixture of the tensile testing machine, starting the equipment after setting the tensile speed, measuring and recording the maximum tensile force when the sample breaks, and calculating the tensile strength (MPa).
[0043] Heat resistance test: Heat resistance test is carried out according to GB / T 17391-1998 Determination of thermal properties of plastics - Heat deformation temperature. The test equipment is a heat deformation temperature tester, the experimental conditions are a heating rate of 120℃ / h, a sample size of 80mm×10mm×4mm, and a load of 1.82MPa. The test steps include clamping the sample in the tester, applying a standard load of 1.82MPa, setting the heating rate to 120℃ / h and starting the equipment, and recording the temperature of the sample when a 1mm deformation occurs as the heat resistance result.
[0044] Surface smoothness test: Surface smoothness test is carried out according to GB / T 18514-2001 Determination of plastic surface roughness. The test equipment is a surface roughness meter, and the experimental conditions are sampling area 20mm×20mm, measurement length 5mm, and measurement speed 0.5mm / s. The test steps include fixing the sample on the test platform of the surface roughness meter, setting the measurement parameters and starting the equipment, and recording and calculating the surface roughness value (Ra) as the result of surface smoothness.
[0045] The finished product material prepared in Example 1 was tested, wherein Comparative Example 1 was a commercially available product, and the experimental method was as follows:
[0046] Table 1
[0047] Performance Indicators Comparative Example 1 Example 1 Wear resistance(mg) 30 15 Tensile strength(MPa) 80 120 Heat resistance(℃) 250 320 Surface smoothness(nm) 50 10
[0048] It can be seen from the experimental results that Example 1 has significant advantages over Comparative Example 1. First, in terms of wear resistance, Example 1 exhibits more excellent durability, indicating that it is more durable under friction conditions. Secondly, in terms of tensile strength, the material of Example 1 exhibits higher strength, indicating that it is stronger and more reliable when subjected to tensile forces. In addition, in terms of heat resistance, the material of Example 1 is able to maintain its mechanical properties at higher temperatures, indicating that it has better thermal stability. Finally, Example 1 also shows better results in surface smoothness, which means that its surface is smoother and suitable for application scenarios that require fine processing. These advantages together show that Example 1 is superior to the comparative example in multiple key performance indicators, demonstrating higher material performance and application value.
[0049] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A novel screen made of a novel material that can be partially imidized, characterized in that: The method for preparing the screen comprises the following steps: S1, compounding the metal mesh and the polyester mesh, compounding the metal mesh with a thickness of 50-200 microns and the polyester mesh on a laminating device, using a polyethylene film with a thickness of 1-20 microns as an adhesive, and during the compounding process, ensuring that the metal mesh and the polyester mesh are flat, avoiding any wrinkles or bubbles, to obtain a composite mesh material; S2, preparation of a polyimide precursor coating solution, in a reaction kettle, a polyimide precursor, a thermal bridging agent and a catalyst are mixed in a mass ratio of 2:1:0.1, and stirred at a speed of 1000-4000 rpm for 10-60 minutes using a high-speed stirrer to ensure uniform mixing. After stirring, the mixed solution is heated to 70-90 degrees Celsius for 1 hour to achieve an optimal coating viscosity of the coating solution, thereby obtaining a polyimide precursor coating solution; S3, coating the composite mesh material with a polyimide precursor, and evenly coating the polyimide precursor coating liquid on the surface of the composite mesh material on an automatic scraper. After the coating is completed, a composite mesh coated with a polyimide precursor is obtained; S4, preliminary baking and curing, in which the composite mesh coated with the polyimide precursor is baked in a hot air circulation baking device to partially cure the polyimide precursor to form a preliminary solid film, and then baked to obtain a partially cured composite mesh; S5, ion beam regional bombardment, in the vacuum ion beam bombardment equipment, the partially solidified composite mesh surface is bombarded with ion beams, and the bombardment parameters are set to ion energy of 1000-2000eV and beam current density of 0.4-0.6mA / cm 2 , the time is controlled within 15 minutes, the bombardment of the ion beam acts selectively on the target area, changing the chemical reactivity of each area, preparing for the subsequent imidization treatment, and obtaining the composite mesh treated with the ion beam; S6, local high-temperature secondary heating, performing local high-temperature heating treatment on the composite mesh treated by the ion beam, using an infrared heating device to heat the target area to 250 degrees Celsius, and maintaining it for 5 minutes, so as to promote the imidization reaction of the polyimide precursor in each area, and after heating, obtain a composite mesh with a local imidization area; S7, ion beam assisted imidization treatment, on the composite mesh with local imidization area, ion beam equipment is used again for auxiliary treatment to further control the depth and range of imidization reaction, the ion beam energy is increased to 1200 eV, and the beam density is controlled at 0.7 mA / cm 2 , the treatment time is extended to 20 minutes. After this step, the chemical structure of the imidization area is more stable, and a composite mesh yarn is obtained after ion beam assisted treatment.
2. The novel screen made of the novel material capable of partial imidization according to claim 1, characterized in that: Also includes: S8, precise forming of polyimide film, in a high-temperature pressing device, the composite mesh that has undergone ion beam assisted treatment is subjected to overall high-temperature pressurization treatment, the temperature is set to 300 degrees Celsius, the pressure is set to 10MPa, and the duration is 30 minutes. Through high-temperature pressurization, the polyimide film is fully formed on the entire surface of the composite mesh, and has excellent wear resistance and structural stability, thereby obtaining a formed polyimide film composite mesh.
3. The novel screen made of the novel material capable of partial imidization according to claim 2, characterized in that: Also includes: S9, laser cutting pattern, in the laser cutting equipment, the formed polyimide film composite mesh is cut according to the pre-set pattern, the laser power is set to 20W, the cutting speed is 0.1 m / s, and the cutting accuracy is controlled at ±10 microns. After laser cutting, a polyimide film composite mesh with a high-precision pattern is obtained.
4. The novel screen made of the novel material capable of partial imidization according to claim 3, characterized in that: Also includes: S10, finished product screen inspection and trimming, quality inspection and trimming of the polyimide film composite mesh with high-precision graphics, use a high-precision microscope to detect the graphics accuracy, check for flaws or cracks, repair or reprocess unqualified areas to ensure product quality, and obtain a new screen product that meets high-precision standards after inspection and trimming.
5. The novel screen made of the novel material capable of partial imidization according to claim 1, characterized in that: In step S1, the temperature of the pressing equipment is set to 150 degrees Celsius, the pressure is 5 MPa, and the pressing time is controlled to 30 minutes.
6. The novel screen made of the novel material capable of partial imidization according to claim 1, characterized in that: In step S3, the scraping speed of the automatic scraping equipment is controlled at 0.5 m / min, and the scraping thickness is controlled at 20 μm, ensuring that the coating liquid covers the entire mesh surface without bubbles or unevenness.
7. The novel screen made of the novel material capable of partial imidization according to claim 1, characterized in that: In step S4, the baking temperature of the hot air circulation baking equipment is set to 150 degrees Celsius, and the baking time is 60 minutes.
Citation Information
Patent Citations
Preparation method of polyimide solar screen printing plate
CN111516368A
Polyimide solar net plate and preparing method thereof
CN111605300A
Complementary artificial synaptic array and electrofluid jet printing preparation method thereof
CN114975778A
High-strength silk-screen mask screen and preparation method thereof
CN115648827A
Forming polyimide coatings by screen printing
CN1170474A